2018
DOI: 10.1371/journal.pone.0205182
|View full text |Cite
|
Sign up to set email alerts
|

Reference genes selection for quantitative gene expression studies in tea green leafhoppers, Empoasca onukii Matsuda

Abstract: Empoasca onukii Matsuda is one of the most devastating pests of the tea plant (Camellia sinensis). Still, the presumed expression stability of its reference genes (RGs) has not been analyzed. RGs are essential for accurate and reliable gene expression analysis, so this absence has hampered the study of the insect’s molecular biology. To find candidate RGs for normalizing gene expression data, we cloned ten common housekeeping genes from E. onukii. Using the ΔCt method, geNorm, NormFinder and BestKeeper, we scr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 61 publications
(54 reference statements)
2
6
0
Order By: Relevance
“…α-TUB is the main component of microtubules that form the cytoskeleton structure, which plays an important role in several eukaryotic cellular processes, including cell mobility and division, and intracellular trafficking 29 . Our results are consistent with previous studies reporting that α-TUB was stable for developmental stages, sexes, tissues, temperature and photoperiod stresses in Empoasca onukii 8 , among various tissues from Coleomegilla maculata 30 and Mythimna separata 24 , for different temperatures in Phenacoccus solenopsis 31 as well as for developmental stages, tissues and sexes in Hermetia illucens 32 . The RPL12 gene encodes a structural protein of ribosomes and is involved in protein translation 33 .…”
Section: Experimental Conditionsupporting
confidence: 93%
See 2 more Smart Citations
“…α-TUB is the main component of microtubules that form the cytoskeleton structure, which plays an important role in several eukaryotic cellular processes, including cell mobility and division, and intracellular trafficking 29 . Our results are consistent with previous studies reporting that α-TUB was stable for developmental stages, sexes, tissues, temperature and photoperiod stresses in Empoasca onukii 8 , among various tissues from Coleomegilla maculata 30 and Mythimna separata 24 , for different temperatures in Phenacoccus solenopsis 31 as well as for developmental stages, tissues and sexes in Hermetia illucens 32 . The RPL12 gene encodes a structural protein of ribosomes and is involved in protein translation 33 .…”
Section: Experimental Conditionsupporting
confidence: 93%
“…Although β-ACT and ArgK are traditional reference genes and have been used in many gene expression studies, they are not always stably expressed. Consistent with our results, many studies have shown unstable expression of β-ACT under variable conditions in a variety of species, including Bemisia tabaci 40 , M. separata 35 , F. occidentalis 39 , Henosepilachna vigintioctopunctata 41 , P. japonica 38 , Hippodamia convergens 42 and C. maculata 30 , as well as for ArgK in Spodoptera litura 43 , P. japonica 38 , C. maculata 30 and E. onukii 8 .…”
Section: Experimental Conditionsupporting
confidence: 92%
See 1 more Smart Citation
“…Multiple RGs have been suggested for normalizing target gene expression, which will reduce the probability of biased normalization 13,48 . In the current study, our results demonstrated using multiple RGs simultaneously in qRT-PCR analysis would increase the sensitivity of gene expression in E. onukii infested leaves (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The selected environmental conditions ranged from biotic to abiotic treatments. Biotic conditions included developmental stage, tissue and sex, which were commonly used in the study of reference genes stability [23, 26, 27]. Abiotic conditions included food, heavy metals and antibiotics.…”
Section: Introductionmentioning
confidence: 99%